The obedience of medical personnel to using personal protective equipment in preventing the transmission of COVID-19 at a private hospital in Indonesia - Hartuti, Eka Putri; Suryani, Dyah; Edwin, Vebby Amellia; Maretalinia, Maretalinia; Suyitno, Suyitno (YCAB Publisher & IAKMI SULTRA, 2021)
Background: As one of the vulnerable groups to be infected by COVID-19, healthcare workers are required to obey the hospital rules and protocols. However, it may remain challenging for them, especially related to the provision of using personal protective equipment.Objective: This study examined the obedience of medical personnel to personal protective equipment in preventing the transmission of COVID-19 at PKU Muhammadiyah Hospital Yogyakarta, Indonesia.Methods: This cross-sectional study examined 259 medical personnel (medical doctors, nurses, and midwives) in the hospital. Descriptive statistics, Chi-Square test, and multiple logistic regression were used for data analysis.Results: The majority of respondents were nurses (80.3%) and female (63.3%). Those who had a poor attitude would be three times more likely to have poor obedience to using personal protective equipment (Adj. OR: 2.81, 95% CI: 1.52 - 5.19). Sex, age, length of work, level of knowledge, level of motivation, and facility support were not correlated with obedience to using personal protective equipment.Conclusion: The finding reported that many medical personnel were not obedient to using personal protective equipment because their response to disease prevention was poor. The results can be used for further intervention and education or training programs for medical personnel.